2009
DOI: 10.1021/ja901156x
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Molecular Conductivity

Abstract: We demonstrate the switchability of the molecular conductivity of a citrate. This was made possible through mechanical stretching of two conformers of such citrate capped on and linked between gold nanoparticles (AuNPs) self-assembled as a film. On the basis of experimental results, theoretical analysis was conducted using the density function theory and Green's function to study the electron flux in the backbone. We found that the molecular conductivity depended on the pathways of electrons that were controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
(36 reference statements)
2
21
0
Order By: Relevance
“…The time span for pinning, t p , during which the droplet edge was located at the desired position on the sample, amounted from 5 to 90 s. As a result of the pinning process, (8) and controlled with a sensor (9). After the pinning procedure, the sample was moved with constant velocity, v s , by a motorized translation stage (10). Correspondingly, the droplet edge with the assembled NPs moved with similar velocity into the direction of the nanogap.…”
Section: Positioning Of Nanoparticle Chains In Between Nanogap Electrmentioning
confidence: 99%
See 2 more Smart Citations
“…The time span for pinning, t p , during which the droplet edge was located at the desired position on the sample, amounted from 5 to 90 s. As a result of the pinning process, (8) and controlled with a sensor (9). After the pinning procedure, the sample was moved with constant velocity, v s , by a motorized translation stage (10). Correspondingly, the droplet edge with the assembled NPs moved with similar velocity into the direction of the nanogap.…”
Section: Positioning Of Nanoparticle Chains In Between Nanogap Electrmentioning
confidence: 99%
“…Consequently, the original molecular levels broaden and shift compared to a free molecule in vacuum. For covalently linked citrate molecules on the gold surface, the broadening can be several hundred meV [10]. Figure 4.4 demonstrates that, for charge transport across a chain of nanoparticles and across a single particle configuration, several channels can be identified.…”
Section: Analysis Of the Conductivity In Chain Of Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrate represents a common electrostatically stabilizing agent for gold NPs, because the particles are typically synthesized through a citric acid reduction reaction [4]. Switching of the molecular conductance of citrate was demonstrated by Wang et al [5], where they used mechanical stretching of two conformers of citrate capped on and linked between the gold NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] The combination of the chemical sensing capabilities of DNA and the electrical properties of CNT in a hybrid nanodevice has been proposed for very sensitive detection of chemical events at the single-molecule level 17,18 and a molecular understanding of CNT-DNA interaction can yield new insights to develop devices for rapid DNA sequencing 19,20 as well as to improve the development of nanosensors, especially for chemical and biological agents. 5,8,[21][22][23][24][25][26][27][28] Gowtham et al 29 studied the physisorption of individual nucleobases on graphene using DFT methods, finding significant differences between interaction strengths when a nucleobase is physisorbed on graphene; based on an analysis of binding energies, they suggested that the base molecule polarizabilities are the main factors determining the nucleobase-graphene interaction strength. In another study by the same authors, the strength of the interaction was analyzed between DNA bases and a small diameter carbon nanotube of chirality (5,0).…”
Section: ' Introductionmentioning
confidence: 99%